Early Outcomes of Pelvic Trauma Patients - Complications, ICU Stay and Treatment Concepts in Two ATLS Compliant Trauma Centers: Germany and Qatar - Keil, Holger; El-Menyar, A.; Daerr, J.; Weil, F.; Abdelrahman, H.; Alhammoud, A.; Ghouri, S.; Babikir, E.; Wahlen, B. M.; Al-Thani, H.; Gruetzner, P. A.; Muenzberg, M. (Acta Chirurgiae Orthopaedicae Et Traumatologiae Cechoslovaca, 2021)
PURPOSE OF THE STUDY
CRIS-Team WoS Importer:2022-06-17